2016
DOI: 10.1080/19443994.2016.1172987
|View full text |Cite
|
Sign up to set email alerts
|

Composition and reversibility of fouling on low-pressure membranes in the filtration of coagulated water: insights into organic fractions behaviour

Abstract: The primary problem for the application of microfiltration (MF) and ultrafiltration (UF) membrane technology is membrane fouling. Such is the case that understanding membrane fouling has become one of the major factors driving MF and UF membrane technology for- ward. Nevertheless, identifying the constituents that most contribute to membrane fouling 20 and quantifying how they are detached when backwashing (BW) and cleaning-in-place (CIP) are applied still remains a challenging task. The aim of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, no potential health risk was recorded with 4 minutes of application of NaOCl reagent, a 120 minutes backwash interval, a 20 LMH backwash flux, and 25 mg/L of reagent concentration [419]. Gibert et al [420] found that high transmembrane pressures, and lower frequency and prolonged durations of chemical backwashing effectively removed foulants.…”
Section: Chemical Membrane Cleaningmentioning
confidence: 99%
“…However, no potential health risk was recorded with 4 minutes of application of NaOCl reagent, a 120 minutes backwash interval, a 20 LMH backwash flux, and 25 mg/L of reagent concentration [419]. Gibert et al [420] found that high transmembrane pressures, and lower frequency and prolonged durations of chemical backwashing effectively removed foulants.…”
Section: Chemical Membrane Cleaningmentioning
confidence: 99%